Questioning the role of sparse coding in the brain. Issue 7 (July 2015) - Spanne, Anton; Jörntell, Henrik
Highlights Sparse coding is questioned on both theoretical and experimental grounds. Generalization is important to current brain models but is weak under sparse coding. The beneficial properties ascribed to sparse coding can be achieved by alternative means.